2012
DOI: 10.5539/sar.v1n2p292
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Influencing Discontinuance of Technology Adoption: The Situation with Some Nigerian Farmers

Abstract: The study identified the factors influencing the discontinuance of improved rice technologies in Nasarawa State of Central Nigeria. Multi-stage random sampling was purposely used to select eighty rice farmers from four rice-producing villages of the study area using structured interview schedule on the respondents. Statistical analysis involving frequency counts, means and percentage were used to satisfy objectives 1, 2, 3, and 4 while regression analysis was applied to satisfy objective 5. The results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 2 publications
4
9
0
Order By: Relevance
“…The number of extension visits to farmers' fields and visits by farmers to demonstration plots/AROC centres was observed to increase confidence and knowledge of farmers towards technologies that were offered, thereby increasing the level of adoption of new technologies. The result agrees with [28,29,30] who advanced that the increasing the number of contacts in an extension programme had a positive and significant effect on the application of agricultural technology. The finding further bears rich parallels to those of [31] who opined that extension (and advisory services), are not merely there to influence farmers physical input but more importantly to initiate a needed change in behaviour and attitudes towards the environment and relating modern inputs.…”
Section: Respondents' Socio-economic Determinants Of Level Of Adoptiosupporting
confidence: 89%
“…The number of extension visits to farmers' fields and visits by farmers to demonstration plots/AROC centres was observed to increase confidence and knowledge of farmers towards technologies that were offered, thereby increasing the level of adoption of new technologies. The result agrees with [28,29,30] who advanced that the increasing the number of contacts in an extension programme had a positive and significant effect on the application of agricultural technology. The finding further bears rich parallels to those of [31] who opined that extension (and advisory services), are not merely there to influence farmers physical input but more importantly to initiate a needed change in behaviour and attitudes towards the environment and relating modern inputs.…”
Section: Respondents' Socio-economic Determinants Of Level Of Adoptiosupporting
confidence: 89%
“…Probit analysis showed that extension frequency significant effected to the technology adoption. Further Bello et al (2012) identified the factors that affected of rice technology discontinuation at Nasarawa, central Nigeria. Characteristics of farmers such as extension contact accounted for 67.0% of the variation in the termination of rice technology adoption by farmers.…”
Section: Frequency Followed the Agricultural Extensionmentioning
confidence: 99%
“…Research Bello, Salau, and Ezra (2012) that identified the factors that affected of rice technology discontinuation at Nasarawa, central Nigeria. Household size accounted for 67.0% of the variation in the termination of rice technology adoption by farmers.…”
Section: Number Of Household Membersmentioning
confidence: 99%
“…The number of family members also positively affected the level of technical efficiency of rice farms in ICMFS program. Research of Bello et al (2012), which identified factors affecting the use of rice farming technology in Nasarawa, Central Nigeria. Characteristics of farmers such as age, size of household, social participation, agricultural experience, land area, income of farms and extension contacts, explained 67.0% of variation in the application of rice technology by farmers.…”
Section: Factors Affecting Technical Efficiencymentioning
confidence: 99%